Design approach for solar cell and battery of a persistent solar powered GPS tracker. (21st July 2017) - Sahraei, Nasim; Watson, Sterling M.; Pennes, Anthony; Peters, Ian Marius; Buonassisi, Tonio
Abstract: Sensors with wireless communication can be powered by photovoltaic (PV) devices. However, using solar power requires thoughtful design of the power system, as well as a careful management of the power consumption, especially for devices with cellular communication (because of their higher power consumption). A design approach can minimize system size, weight, and/or cost, while maximizing device performance (data transmission rate and persistence). In this contribution, we describe our design approach for a small form-factor, solar-powered GPS tracker with cellular communication. We evaluate the power consumption of the device in different stages of operation. Combining measured power consumption and the calculated energy-yield of a solar cell, we estimate the battery capacity and solar cell area required for 5 years of continuous operation. We evaluate trade-offs between PV and battery size by simulating the battery state of charge. The data show a trade-off between battery capacity and solar-cell area for given target data transmission rate and persistence. We use this analysis to determine the combination of solar panel area and battery capacity for a given application and the data transmission rate that results in minimum cost or total weight of the system.